Discourse and practice of ethics in public administration in Colombia (2015)
This work has like object, the conceptual analysis of ethics in the field of Public Administration in Colombia. The analysis answers the following questions: ¿The ethics is present in the actions of the civil service? and ¿The public officials have the profile to assume its sense of belonging in his institutional work? The importance of this document is his great theoretical value that allows us to understand the speech and ethics in public administration, principles like missionary entities of the Colombian State. Taking ethics as limiting moral discipline and how to act socially official in the public administration and as the essence of the institutional principles inherently executed by those who respect the public, I had analyzed documents of different authors who argue important concepts about this topic. It is evident that although there are several mechanisms to prevent individuals holding public office commit disciplinary offenses and crimes against the public administration, the Colombian government fails to reduce the high levels of public corruption. The act ethically in public administration, is largely achieved if citizens, especially to the younger generations, are educated from his early life with discipline, commitment and respect for the public objects like a part of the daily training, without ruling out that this is a fairly complex task not only for the training at home, but also in educational training institutions and other social spaces for training